Trends in Perception of Psychosocial School Environment: HBSC Study 2002-2014 in the Czech Republic - Vašíčková, Jana; Hollein, Tomáš; Sigmund, Erik; Salonna, Ferdinand; Boberová, Zuzana (Central European journal of public health, 2017)
OBJECTIVE: School is a place where students spend most of their daytime hours. Previous studies indicate that the class climate significantly affects students in both positive and negative ways. The aim of our study is to describe the trends in the psychosocial school environment based on four surveyed years in the Czech Republic. METHODS: The trends in perception of school were assessed by the standardised self-reported HBSC questionnaire from data collected in 2002, 2006, 2010, and 2014. The overall sample included 8,530 girls and 8,087 boys. Data was analysed separately by gender and three age categories 11, 13, and 15 years. Trends were calculated using descriptive categories and percentages. To identify factors influencing school likeness we used binominal logistic regression. RESULTS: Results showed that school satisfaction declines with age both in boys and girls in each of four surveyed periods. Students who do not feel a high level of support from the teacher are more prone to negative perceptions of school. School duties in both genders were perceived to be greater and more stressful in 2014 than in 2002. CONCLUSIONS: Interventions to support the perception of psychosocial school environment via the educational system should, therefore, take the aforementioned variation into account.
Keywords: longitudinální studie; Cross-Sectional Studies; zdravé chování; mladiství; Česká republika; školy; mužské pohlaví; studenti; průřezové studie; osobní uspokojení; Czech Republic; sociální prostředí; school pressure; dítě; Child; Schools; ženské pohlaví; teacher's support; Health Behavior; Humans; Social Environment; Students; school environment; sociální opora; HBSC questionnaire; school satisfaction; Social Support; Personal Satisfaction; zdravotnické přehledy; Longitudinal Studies; Female; classmate relationship; Adolescent; lidé; Male; Health Surveys